Does Envy, Self Esteem and Social Norms on Instagram Lead to Conspicuous Consumption and Overspending? - Canan Yılmaz Uz; Nur Özer Canarslan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The purpose of this study is to investigate how envy of others affects the conspicuous consumption and overspending habits of Instagram users. Additionally, the study aims to examine the effect of self-esteem and social norms on conspicuous consumption and overspending. This empirical study used a proposed model, which was tested through the distribution of questionnaires to a sample of 346 Turkish Instagram users. Path analyses were performed to validate the research hypothesis. The study findings elicited the effect of Instagram users’ envy towards others has a significant and positive effect on both conspicuous consumption and overspending. Additionally, the study found that injunctive norms, which reflect the perceived social approval or disapproval of others, have a direct and positive effect on conspicuous consumption. On the other hand, descriptive norms, representing the perception of others' actual behavior, did not have a direct effect on conspicuous consumption. Regarding self-esteem, the results did not support the hypothesis that self-esteem has a direct and positive effect on conspicuous consumption. Furthermore, the study found a significant and positive relationship between conspicuous consumption and overspending, indicating that individuals who engage in conspicuous consumption are more likely to exceed their budget limits and engage in impulsive buying behaviors.